Test Case Prioritization Based on Early Fault Detection Technique - Yadav, Dharmveer K.; Dutta, Sandip (Recent Advances in Computer Science and Communications, 2021)
Background: In Regression testing when any changes made to already tested program it should not affect to other part of program. When some part of code is modified then it is necessary to validate the modified code. In the life cycle of software development, regression testing is an important and expensive activity. Objective: Our objective is to save regression testing time by reducing the cost and time of retesting of the modified code as well as affected components of the program. Objective is to prioritize the test case for object oriented program based on early fault detection. Methods: A new model is proposed using fuzzy inference system for regression testing. This paper presents a fuzzy inference system based on the use of inputs like fault detection rate, execution time and requirement coverage. The proposed system allows tester to prioritize test case based on linguistic rules. Results: In this paper performance is measured by using Average Percentage Fault Detection metric. We analysed for both prioritized and non-prioritized test suite using average percentage fault detection metric. Conclusion: We developed fuzzy expert model which helps to takes better decision than other expert system for regression testing. We conclude that, prioritization of test case will decrease the regression testing time.
Keywords: fault detection rate